The Effect of Increasing Catalyst Concentration of Fabricated Hydrogen Generator on Proton Exchange Membrane Fuel Cell Performance - M Anis Mustaghfirin; Mardi Santoso; M Hakam; Rafi Akbar Heriyansyah; Aminatus Sa’diyah; Eky Novianarenti; Ni’matut Tamimah; Haidhar Wahyu S (Surabaya State Polytechnic of Shipbuilding, 2024)
Hydrogen can be utilised through a Proton Exchange Membrane Fuel Cell (PEMFC) which has many advantages, namely more energy yield, higher energy density, no emissions, and no need for recharging compared to using batteries. The highest electrolyzer efficiency results were found on the 0.05M KOH catalyst with a value of 1.70% and it can be concluded that the higher the catalyst concentration, the higher the electrolyzer efficiency. The highest power density and fuel cell efficiency quality is found in the 0.05M NaCl catalyst but with the lowest Specific Fuel Consumption (SFC) of 0.62 kg/kWh, this indicates that the relationship between concentration and power density and fuel cell efficiency is directly proportional while it is inversely proportional to Specific Fuel Consumption ( SFC). The best Break Even Ratio value is found in the NaCl catalyst type 0.05 with a value of 0.082. The use of a seawater catalyst has the highest efficient value at a percentage of 100% with electrolyzer efficiency reaching 13.36% and the lowest SFC, namely 0.24 kg/kWh. Based on these results, the use of hydrogen generators for Proton Exchange Membrane Fuel Cells (PEMFC) needs to be developed.